Hengli® Chinese Botulinum Toxin Type A for Treatment of Patients With Overactive Bladder: A Multicenter, Prospective, Randomized, Double-Blind, Placebo-Controlled Trial - Liao, Limin; Liu, Qinggang; Cong, Huiling; Xu, Zhihui; Li, Enhui; Weng, Zhiliang; Jiang, Haihong; Liu, Ben; Huang, Xiao; Xia, Shujie; Wen, Wei; Wu, Juan; et al. (Frontiers in Pharmacology, 2022)
Objective: To evaluate the efficacy and safety of Hengli® Chinese botulinum toxin type A (BTX-A; 100 U) in Chinese patients with overactive bladder. Methods: This study was a multicenter, randomized, double-blind, placebo-controlled trial in Chinese patients who were inadequately managed with anticholinergic medications. Eligible patients were randomized 2:1 to receive intradetrusor injections of Hengli® BTX-A (n = 144) or placebo (n = 72). The primary endpoint was the change in the number of daily micturition episodes at week 6 from baseline. The secondary efficacy endpoints included the average frequency of urgency and urinary incontinence (UI) episodes per day, urgency score, average micturition volume per day, OABSS, and QoL score. Results: In the Hengli® BTX-A group, there was a significantly greater reduction in the average number of micturition episodes per 24 h compared with the placebo group (3.28 vs. 1.43; P = 0.003). Moreover, there was a significantly greater improvement in the daily number of urgency episodes, micturition volume, and OABSS score. An increased post-void residual urine volume, dysuria, and urinary tract infection represented adverse events (AEs) in the Hengli® BTX-A group. Most AEs were mild or moderate in severity. One patient in the BTX-A group initiated clean intermittent catheterization (CIC) during treatment. Conclusions: Hengli® BTX-A treatment was well-tolerated and resulted in significant improvements in OAB symptoms among Chinese patients inadequately managed by anticholinergics. Clinical Trial Registration: http://www.chinadrugtrials.org.cn/clinicaltrials.prosearch.dhtml, Identifier: CTR20131190.